Cardiac Tamponade from Purulent Pericarditis due to Cutibacterium acnes. (18th November 2018) - Farhat-Sabet, Ardalon; Hull, Robert; Thomas, Dustin
Abstract : Purulent pericarditis is a potentially fatal disease with high mortality rates if untreated. Cutibacterium acnes (formerly Propionibacterium acnes ) is an anaerobic bacteria that is ubiquitous in skin flora and is commonly thought of as a culture contaminant; however, it does have pathogenic potential. We present a case of purulent pericarditis secondary to C. acnes leading to cardiac tamponade. Initial stabilization and diagnosis were made via pericardiocentesis; afterward the patient underwent a pericardial window. Due to a severe penicillin allergy, he was successfully treated with a 14-day course of vancomycin. To our knowledge, this represents only the third published case of purulent pericarditis with cardiac tamponade caused by C. acnes and the first case treated with a 14-day course of vancomycin.